A 10‐year longitudinal follow‐up study of a U.K. paediatric transplant population to assess for skin cancer3. (28th August 2018) - Foo, S.H.; Nightingale, P.G.; Gazzani, P.; Bader, E.; Ogboli, M.; Martin‐Clavijo, A.; Milford, D.V.; Kelly, D.A.; Moss, C.; Thomson, M.A.
Summary: Background: Our earlier study, published in 2004, 1 found no skin cancer in a cohort of paediatric organ transplant recipients (POTRs) 5–16 years post‐transplantation. We re‐evaluated the same cohort 10 years later. Objectives: To determine the prevalence of premalignant and malignant skin lesions and identify known risk factors associated with melanocytic naevi in a U.K. paediatric transplant population. Methods: Ninety‐eight POTRs from the original 2004 study were invited to participate in this longitudinal follow‐up study. History of sun exposure, demographics and transplantation details were collected using face‐to‐face interviews, questionnaires and case note reviews. Skin examination was performed for regional count of malignant lesions, benign and atypical naevi. Results: Of the 98 patients involved in the initial study, 45 POTRs (eight kidney, 37 liver), with a median follow‐up of 19 years (range 15–26 years), agreed to participate. Neither skin cancer nor premalignant lesions were detected in these patients. When compared with the 2004 cohort, 41 patients in our current cohort had increased numbers of benign naevi ( P < 0·001) with 11 patients having ≥ 50 benign naevi. Seventy‐one per cent of benign naevi in our 2014 cohort occurred on sun‐exposed sites (13% head/neck, 35% arms and 23% legs). Patients who regularly used sunscreen had more benign naevi on their arms ( P = 0·008). Conclusions: Although skin cancer was not observed in our cohort, we identified a significant increase in the number of benign naevi, particularly in those reporting frequent sunburn and sunscreen use. Abstract : What's already known about this topic? Organ transplant recipients are at increased risk of skin cancer owing to the immunosuppressive treatment given to prevent organ rejection. The incidence of skin cancer in paediatric transplant recipients is unknown, although it is recognized to be different from that in adult recipients. Increased naevus count and sunburn episodes are risk factors for melanoma. What does this study add? No skin cancer was observed in this lengthy longitudinal follow‐up study of a U.K. paediatric transplant patient cohort (15–26 years post‐transplantation). There is a significant increase in the number of patients with benign naevi counts ≥ 50 in our paediatric transplant patient cohort compared with the normal population. Patients who received organ transplants in childhood lack sun awareness, take sunny holidays abroad, use sunbeds and experience sunburn. Linked Editorial: Coughlin and Siegel. Br J Dermatol 2018;179 :1235–1236 . Plain language summary available online Respond to this article